ANALISIS STAKEHOLDER DALAM PROGRAM GIZI PADA BALITA DI PUSKESMAS KAMPAR: Stakeholders Analysis in the Nutrition Program for Toddlers in Kampar Health Center - kartini Ega; Kiswanto Kiswanto; Ahmad Hanafi; Nurmaimun Nurmaimun; Novita Rany (Jurnal Kesehatan Komunitas, 2020)
ABSTRACT The role of stakeholders in reducing the number of malnutrition is very influential in efforts to prevent the occurrence of nutritional problems in toddlers. Riau Province ranks 20th with the percentage of malnutrition as much as 4.20% and the percentage of malnutrition as much as 14%. Data from the Kampar District Health Office in 2018 found that Kampar Health Center occupies the highest number for malnutrition in children under five with a percentage of 1.6% or as many as 33 people. This study aims to obtain in-depth information about the role of stakeholders in the Nutrition Program for Toddlers in the Kampar Health Center in 2019. This study is qualitative in nature with the Rapid Assessment Procedure research design, namely in-depth direct interviews of the study sample. The number of samples in this study amounted to 10 people, of which 5 people as the main informant and 5 people as supporting informants. The results of the study found that stakeholders have exercised their power in accordance with their main duties, functions and roles, only that the workload has not been evenly distributed and there is still a lack of cooperation with development business partners. Conclusion power has been going well according to the main tasks, functions and roles, interests or interests in establishing cooperation with business development partners is not optimal, the position in setting the target to be achieved has gone well. It is recommended that the puskesmas be able to analyze the workload of employees, be able to do an analysis of the needs of Human Resources (HR) and establish cooperation with development business partners Key word : Stakeholders, Nutrition for Toddlers Program, Health Center